The Role of Electronic Customs Systems in Ensuring Transparency and Efficiency of Cross-Border Trade Operations - Okhrimenko Oksana; Охріменко О.; Olena Volkova; Олена Волкова (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. On the background of unstable worldwide trade and rising significance of digital technologies in public administration, customs procedures modernization gains a strategic importance for many economies. As a geographically relevant crossroads of Western and Eastern markets, adoption of electronic customs systems for Ukraine is essential for realization of openness, efficiency and transparency in cross border trade operations. This article looks into the influence of the electronic customs system implementation for Ukraine in respect to the trade openness and customs efficiency during the time period of 2020-2024. The objective of the study is to assess the degree to which the digital customs transformation adds to the improvement of the country's trade performance in eliminating bureaucratic barriers and enhancing faster and reliable customs processes. Methodology of this research is used to quantify the direct and indirect effects of electronic customs penetration on the most important trade related outcomes: a simultaneous equations model is designed and several dynamic panel estimation techniques are employed in order to improve treatment of unobserved heterogeneity and to estimate with more precision the effects of interest. The model consists of macroeconomic controls (GDP growth rate, exchange rate volatility, inflation and FDI inflows) and structural variables (digital infrastructure, institutional readiness and government policy incentives). The results indicate statistically significant positive relationship of an increase in the proportion of electronically processed customs declarations on trade openness while reducing customs clearance times. Also, digital readiness of infrastructure and quality of policy implementation are proven to be vital mediating variables which contribute to the effect of electronic customs systems. The empirical results are compared with the previous international research and show that Ukraine’s digital customs reforms are state-of-the art in comparison with the global best practices and theoretical expectations. These results are explained in frameworks of institutional and transaction cost economics in order to explain how digital tools can reduce inefficiency, increase compliance, and increase operational transparency. The statistical tests relevant to endogeneity and model specification are shown to provide support for the robustness of the findings. Finally, this article shows that the adoption of the electronic customs systems has greatly increased openness and efficiency in Ukraine’s cross border trade during the studied period. These findings stress the need to keep investing in customs digitalization, institution capacity building, and international cooperation. Further research prospects include the examination of regional differences in the adoption of the system, the embedding of new technologies such as blockchain and the economic effects of the digital customs reforms.

Az instabil világkereskedelem és a digitális technológiák állami irányításban betöltött szerepének növekedése miatt a vámeljárások modernizálása stratégiai jelentőséget nyer számos gazdaság számára. Az elektronikus vámrendszerek bevezetése Ukrajna számára fontos a nyitottság, a hatékonyság és a határon átnyúló kereskedelmi műveletek átláthatóságának megvalósítása szempontjából, mivel az ország földrajzilag a nyugati és keleti piacok kereszteződésében fekszik. A cikk az elektronikus vámrendszer bevezetésének hatását vizsgálja Ukrajnában a kereskedelem nyitottságára és a vámhatóság hatékonyságára a 2020–2024 közötti időszakban. A kutatás célja annak értékelése, hogy a digitális vámátalakítás milyen mértékben járul hozzá az ország kereskedelmi mutatóinak javulásához a bürokratikus akadályok eltávolításával, valamint a vámeljárások gyorsaságának és megbízhatóságának növelésével. A jelen tanulmány módszertana az elektronikus vámkezelés közvetlen és közvetett hatásainak számszerűsítésére szolgál a kereskedelem legfontosabb eredményeire: kidolgozták az egyidejű egyenletek modelljét és több dinamikus panel értékelési módszert alkalmaztak a nem megfigyelhető heterogenitás kezelésének javítása és a vizsgált hatások pontosabb értékelése érdekében. A modell makrogazdasági kontrollindikátorokból (GDP-növekedés, árfolyam-volatilitás, infláció és közvetlen külföldi befektetések beáramlása) és strukturális változókból (digitális infrastruktúra, intézményi felkészültség és állami politikai ösztönzők) áll. Az eredmények statisztikailag szignifikáns pozitív összefüggést mutatnak az elektronikus úton feldolgozott vámáru-nyilatkozatok arányának növekedése és a kereskedelem nyitottsága között, a vámkezelés időtartamának csökkenésével. Ezenkívül bebizonyosodott, hogy az infrastruktúra digitális felkészültsége és a politika végrehajtásának minősége létfontosságú közvetítő változók, amelyek elősegítik az elektronikus vámrendszerek hatását. Az empirikus eredményeket összehasonlítjuk korábbi nemzetközi tanulmányokkal, és azt mutatják, hogy az ukrán digitális vámreformok a világ legjobb gyakorlataival és elméleti elvárásokkal összehasonlítva a legkorszerűbbek. Ezeket az eredményeket az intézményi gazdaságtan és a tranzakciós költségek gazdaságtana keretében magyarázzák, hogy a digitális eszközök hogyan csökkenthetik a hatékonyság hiányát, javíthatják a megfelelést és növelhetik a működési átláthatóságot. Kimutatták, hogy az endogenitásra és a modell specifikációjára vonatkozó statisztikai tesztek megerősítik a következtetések megbízhatóságát. Végül, ez a cikk azt mutatja, hogy az elektronikus vámrendszerek bevezetése jelentősen növelte Ukrajna határon átnyúló kereskedelmének átláthatóságát és hatékonyságát a vizsgált időszakban. Ezek a következtetések aláhúzzák annak szükségességét, hogy továbbra is beruházzanak a vámhatóság digitalizálásába, az intézményi kapacitás kiépítésébe és a nemzetközi együttműködésbe. A kutatás további perspektívái között szerepel a rendszer bevezetésének regionális különbségeinek vizsgálata, új technológiák, például a blokklánc bevezetése, valamint a digitális vámreformok gazdasági hatásainak elemzése.

Резюме. В умовах нестабільної світової торгівлі та зростання значення цифрових технологій у державному управлінні модернізація митних процедур набуває стратегічного значення для багатьох економік. Впровадження електронних митних систем для України є важливим для реалізації відкритості, ефективності та прозорості транскордонних торговельних операцій, географічно розташовуючись на перехресті західних та східних ринків. У статті розглядається вплив впровадження електронної митної системи в Україні на відкритість торгівлі та ефективність митниці в період 2020-2024 років. Метою дослідження є оцінка ступеня, до якого цифрова митна трансформація сприяє покращенню торговельних показників країни через усунення бюрократичних бар’єрів і підвищення швидкості та надійності митних процесів. Методологія даного дослідження використовується для кількісного визначення прямих і непрямих впливів проникнення електронної митниці на найважливіші результати, пов’язані з торгівлею: розроблено модель одночасних рівнянь і застосовано декілька методів оцінки динамічної панелі, щоб покращити обробку неспостережуваної неоднорідності та більш точно оцінити ефекти, що представляють інтерес. Модель складається з макроекономічних індикаторів контролю (темп зростання ВВП, волатильність обмінного курсу, інфляція та приплив прямих іноземних інвестицій) і структурних змінних (цифрова інфраструктура, інституційна готовність і стимули державної політики). Результати вказують на статистично значущий позитивний зв’язок збільшення частки електронно оброблених митних декларацій із відкритістю торгівлі при скороченні часу митного оформлення. Крім того, доведено, що цифрова готовність інфраструктури та якість впровадження політики є життєво важливими посередницькими змінними, які сприяють ефекту електронних митних систем. Емпіричні результати порівнюються з попередніми міжнародними дослідженнями та показують, що реформи цифрової митниці в Україні є найсучаснішими порівняно з найкращими світовими практиками та теоретичними очікуваннями. Ці результати пояснюються в рамках інституційної економіки та економіки транзакційних витрат, щоб пояснити, як цифрові інструменти можуть зменшити неефективність, підвищити відповідність і підвищити операційну прозорість. Показано, що статистичні тести, що стосуються ендогенності та специфікації моделі, підтверджують надійність висновків. Дослідження демонструє, що запровадження електронних митних систем значно підвищило відкритість та ефективність транскордонної торгівлі України протягом досліджуваного періоду. Ці висновки підкреслюють необхідність продовжувати інвестувати в цифровізацію митниці, розбудову інституційного потенціалу та міжнародну співпрацю. Подальші перспективи дослідження включають вивчення регіональних відмінностей у прийнятті системи, впровадження нових технологій, таких як блокчейн, та економічні наслідки цифрових митних реформ.
Роль електронних митних систем у забезпеченні відкритості та ефективності транскордонних торгівельних операцій
Az elektronikus vámrendszerek szerepe a határokon átnyúló kereskedelmi műveletek átláthatóságának és hatékonyságának biztosításában
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/9
Keywords: customs efficiency; customs modernization; digital transformation; electronic customs systems; international trade; trade openness; trade policy; Ukraine; virtual assets; functional aspect; investments